Papers and New Species of Minor Insect Orders Published in Zootaxa, 2001–2020 - Bernard, Ernest C.; Whittington, Andrew E. (Zootaxa, 2021)
A summary is presented of papers published on minor insect orders (MIO) in Zootaxa’s first 20 years, as well as the number of new species described therein. The MIO orders currently covered by the editors and summarized here include Archaeognatha (Microcoryphia), Dermaptera, Embioptera, Siphonaptera, Zoraptera and Zygentoma, as well as the hexapod classes Protura and Diplura. Both fossil and extant taxa of these groups are included in the MIO purview. The MIO editors also have frequently served as interim editors for groups temporarily without a subject-matter editor, such as Carabidae, Blattodea and Mantodea; as a backup editor for Mecoptera; and as ad-hoc editors for papers written by the editors of a different taxonomic group or for papers without a single-taxon focus. In the period 2001‒2020, descriptions of 130 new species were published, compared with 816 species in all other journals. The greatest number of species were for Protura (49), while Zoraptera had the highest proportion of papers compared to all publications (50%).